Reassessing supplier reputation in international trade coordination – a German and Australian perspective of global organic food networks - Bernzen, Amelie (DIE ERDE – Journal of the Geographical Society of Berlin, 2014)
Uncertainties are especially high among importing firms and for products with sensitive and ‘critical’ quality characteristics in a societal context, such as food. While much recent literature on this issue has focused on the implementation of standards and certification systems, I argue that reputation also plays an important role for trading firms in mitigating uncertainties across large distances. Reputation may or may not reflect reality and is based on public (e.g. media) and networked (from individuals) information. This article draws on Convention Theory in a case study based on qualitative interviews among organic food importers to Germany and Australia. I first show that the degree of their public exposure implies specific risks and strongly influences importers’ coordination strategy. I then go on to examine how, in these firms’ supplier relations and risk management, not only the reputation of (potential) suppliers counts, but also the reputation of supplier countries and institutional systems such as standards and certification bodies. Intensive involvement and first-hand experience with certifiers and suppliers in exporting countries can, in some cases, cause firms to challenge their existing beliefs. I conclude that a good reputation is still essential for (improving) market access, even when basic prerequisites such as legally mandatory certification are fulfilled.